E-Commerce Application Adoption: Impact of Service Features, Speed of Access, and Customer Complaint Services - Santya, Maria Lenny; Anggoro, Muhammad Agung; Carolyn, Carolyn; Angeline, Angeline (Yayasan Riset dan Pengembangan Intelektual, 2025)
E-commerce refers to buying and selling transactions conducted through electronic media, particularly the internet. Today, e-commerce is increasingly associated with digital technologies and online-based applications. The rapid development in this industry has intensified competition, resulting in some e-commerce platforms achieving top rankings in terms of user adoption, while others have experienced a decline in popularity, such as Blibli.com and Bukalapak. Based on preliminary observations, the decline in consumer decisions to use these e-commerce platforms is suspected to be due to a lack of understanding of service features, issues related to access speed, and the absence of complaint handling services within the applications. This study focuses on the population of all e-commerce users in Medan City, whose exact number is unknown. Therefore, the Lemeshow method was applied to determine the appropriate sample size under conditions of unknown population size, resulting in a total of 96 respondents. The sampling technique used was accidental sampling, in which respondents were randomly selected to participate in the study. The results of the research show that service features significantly influence users’ decisions to use e-commerce applications. In addition, access speed also plays a role in shaping consumer decisions to adopt these platforms. Furthermore, the presence of complaint handling services has a notable impact on usage decisions. Simultaneously, service features, access speed, and complaint handling services collectively affect consumers' decisions in utilizing e-commerce applications.